The Jake show - Levy, Joshua (Joshua S.) (Katherine Tegen Books, an imprint of HarperCollins Publishers, 2023)
"For TV-obsessed Jake Lightman, his parents' divorce is like his favorite show getting canceled: The worst. Now he's stuck between playing the role of 'Yaakov' for his mother and 'Jacob' for his father. On Jake's first day at a new school, Caleb and Tehilla barrel into his life. Suddenly, he has two friends who seem to like the real Jake. And when they invite him to Camp Gershoni for the summer, Jake knows he has to go--even if his parents won't let him. With help from Caleb and Tehilla, Jake concocts a web of lies to get to camp. But he struggles to keep up the ruse--and be a good friend at the same time. As the cost of lying grows, he must decide what's truly important, or risk losing the people he cares about the most."--